2011
DOI: 10.5171/2011.357694
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Benchmarking Practices in Higher Education in Kenya: The Case of Public Universities

Abstract: Benchmarking has been used as a tool, a methodology and a technique for continuous improvements in sectoral operations to gain and maintain competitive advantage. This was a survey of benchmarking practices in higher education in Kenya, the case of public universities, whose objectives were; to document the benchmarking activities in the public universities; to establish the challenges facing the public universities in benchmarking. Cross sectional survey was used in this study to collect data from the six pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…A Survey of benchmarking practices in higher education in Kenya: the case of public universities by Magutu et al (2011) found out that participating in benchmarking would Kenya: The Managers' Perception and Experience give Kenyan public universities a better understanding of practice, process, or performance and insights of the academic operations and functions. The three most critical factors facing the benchmarking processes in Kenya were found to be: time and resource availability; limited duration; comparability and compatibility which happened to be the probable reason why the institutions don't practice international benchmarking.…”
Section: Benchmarking and Performance Improvementmentioning
confidence: 99%
“…A Survey of benchmarking practices in higher education in Kenya: the case of public universities by Magutu et al (2011) found out that participating in benchmarking would Kenya: The Managers' Perception and Experience give Kenyan public universities a better understanding of practice, process, or performance and insights of the academic operations and functions. The three most critical factors facing the benchmarking processes in Kenya were found to be: time and resource availability; limited duration; comparability and compatibility which happened to be the probable reason why the institutions don't practice international benchmarking.…”
Section: Benchmarking and Performance Improvementmentioning
confidence: 99%
“…Among the local studies, [6] focused on benchmarking the order delivery process for continuous improvement in the Kenya oil industry, and [5] documented the benchmarking activities based on the academic function of Kenya public universities, both studies suggested that there was need for a study to be conducted to determine to what extent other companies outside the oil and education industries in Kenya use benchmarking as a continuous improvement tool.…”
Section: Research Problemmentioning
confidence: 99%
“…Sources of benchmarking ideas can be obtained from data centers, libraries or through direct search [4]. [5] concluded that the three critical factors that have influenced the success of public universities' benchmarking practices in their environs are time and resource availability: limited duration, comparability and compatibility, which is the reason why companies do not practice international benchmarking. [6] and [5] also recommended a study towards determining the extent to which other companies and institutions outside the higher education sector have used benchmarking as a tool for continuous improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Sifuna (1998) noted that Kenya has attached education to economic and social development since 1963. This led to the rapid expansion of the education system to provide qualified persons for the growing economic and administrative institutions and to undertake some reforms to reflect the aspirations of an independent state Magutu et al (2011), discuss that over the last four decades, the social demands with respect to higher education in Kenya have clearly intensified. This has been exemplified by the rise in enrolment in public and private universities, the proliferation of more private universities and the establishment of the private wings (self sponsored programmes) in the public universities (Government of Kenya, 2005).…”
Section: Higher Education In Kenya: An Overview Of Issues Challenges and Opportunitiesmentioning
confidence: 99%